Vision Based Tracking and Interception of Moving Target by Mobile Robot Using Fuzzy Control - Boumehraz, Mohamed; Habba, Zineb; Hassani, Rafia (Journal of Applied Engineering Science & Technology, 2018)
This paper presents a simple Fuzzy Logic Controllers (FLC) based control strategy to solve the tracking and interception problem of a moving target by a mobile robot equipped with a pan-tilt camera. Before sending commands to the mobile robot, video acquisition and image processing techniques are employed to estimate the target’s position in the image plane. The estimate coordinates are used by a fuzzy logic controller to control the pan-tilt camera angles. The objective is to ensure that the moving target is always at the middle of the camera image plane. A second FLC is used to control the robot orientation and to guarantee the tracking and interception of the target. The proposed pan-tilt camera and robot orientation controllers’ efficiency has been validated by simulation under Matlab using Virtual Reality Toolbox.